2012
DOI: 10.1371/journal.pone.0052057
|View full text |Cite|
|
Sign up to set email alerts
|

Seasonal Variations of Neuromotor Development By 14 Months of Age: Hamamatsu Birth Cohort for Mothers and Children (HBC Study)

Abstract: The present study aimed at investigating whether neuromotor development, from birth to 14 months of age, shows seasonal, cyclic patterns in association with months of birth. Study participants were 742 infants enrolled in the Hamamatsu Birth Cohort (HBC) Study and followed-up from birth to the 14th month of age. Gross motor skills were assessed at the ages of 6, 10, and 14 months, using Mullen Scales of Early Learning. The score at each assessment was regressed onto a trigonometric function of months of birth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…It is possible that if we followed the children over time, the gap between summer-born group and winter-born group would gradually narrow. A paper by Tsuchiya et al [ 55 ] did find that MDI and PDI score differences were smaller after a longer follow-up period. Second, we are not able to identify the casual relationship between Hb levels and PDI scores by birth season.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that if we followed the children over time, the gap between summer-born group and winter-born group would gradually narrow. A paper by Tsuchiya et al [ 55 ] did find that MDI and PDI score differences were smaller after a longer follow-up period. Second, we are not able to identify the casual relationship between Hb levels and PDI scores by birth season.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the patriating infants who were born in May experience 12 warmer months by 18 months of age, compared to those born in winter. A recent study reported that warmer weather accelerated neurodevelopment during early infancy in general ( 18 ). These facts suggest that infants have higher effortful control and lower aggression if measurements occur in autumn and winter than in other seasons.…”
Section: Discussionmentioning
confidence: 99%
“…As with previous research based on the HBC Study ( 18 ), the 12 months of the year of birth were categorized into four seasons: winter (December, January, and February), spring (March, April, and May), summer (June, July, and August), and autumn (September, October, and November).…”
Section: Methodsmentioning
confidence: 99%
“…Early abnormal or unusual neuromotor development in a child, particularly gross motor development, may indicate a later-appearing neurodevelopmental disorder, regarded as the "dominant domain of neurodevelopment, particularly the first year of life [12]" and a possible early marker for ASD [12,13]. However, like the discrepant findings of birth season effects on neurodevelopmental disorders, the results of a limited number of previous studies on the association between birth month/season and early childhood motor development have also varied across different countries in the northern hemisphere, ranging from winter/ spring-born outperforming others to no association [8,12,[14][15][16]. Tsuchiya et al [12] concluded that among 742 Japanese infants, although the winter/spring-born were more advanced in their motor development at 6 and 10 months of age, the advantage disappeared at 14 months; in contrast, McGrath et al [8] found that among 22,123 American children, the winter/spring-born showed better motor development all the way from 8 months up to 7 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…However, like the discrepant findings of birth season effects on neurodevelopmental disorders, the results of a limited number of previous studies on the association between birth month/season and early childhood motor development have also varied across different countries in the northern hemisphere, ranging from winter/ spring-born outperforming others to no association [8,12,[14][15][16]. Tsuchiya et al [12] concluded that among 742 Japanese infants, although the winter/spring-born were more advanced in their motor development at 6 and 10 months of age, the advantage disappeared at 14 months; in contrast, McGrath et al [8] found that among 22,123 American children, the winter/spring-born showed better motor development all the way from 8 months up to 7 years of age. These discrepancies most likely derive from the small sample size of the studies-less than several hundred participants, except the study by McGrath et al-as well as variation in country, climates, screening tools, and timing of outcome measurements.…”
Section: Introductionmentioning
confidence: 99%